Autologous Bone Flap Resorption Years After Subtemporal Craniotomy. (June 2018) - Obafunwa, John Oladapo; Hammerl, Emily; Jaskierny, David; Taylor, Livia; Russell, Lynette; Reinhard, Karl
Abstract : Abstract: In Spring of 2012, the partially undressed and skeletonized remains of a homeless adult Hispanic male was found in a fairly open wooded area in Nebraska. The remains showed evidence of extensive pathologies, which included healed traumas and surgeries. Examination of the decedent's medical records revealed that he had a history of kidney and liver problems, alcohol abuse, several traumas including a major head injury that necessitated a craniotomy, and radiological features of neurocysticercosis. The autologous bone flap, which was replaced after the craniotomy, had resorbed significantly away from the edges of the injury. Death was variously attributed to craniocerebral injury with hypothermia sequel to blunt force trauma most probably due to a fall. The manner of death was ruled as an accident. This study makes use of the forensic evidence and medical records to examine the possibility that the unique combination of failed cranioplasty, hypothermia, and neurocysticercosis may have contributed to the victim's death. Other potential causes of death are considered.